Correlation of the DRD2 gene polymorphism with psychopathology and predictive antimanic responses in patients with bipolar mania - Tao, Hejian; Jin, Haiying; Xu, Min; Chen, Haihan; Sun, Fengli; Jin, Weidong (Frontiers in Pharmacology, 2024)
To explore the correlation of the DRD2 gene polymorphism with psychopathology and predict responses in patients with mania treated with lithium and olanzapine. Sixty patients with bipolar mania were treated with lithium combined with olanzapine for 8 weeks and assessed using YMRS, HAMD, and HAMA. The DRD2 gene polymorphism rs1800497 was tested. Eleven (24.4%) manic patients achieved an early effective response according to the reduction of the YMRS score of >20% in the 2nd week, with a lower HAMA score than the no early effective response group. Twenty-three (51.1%) manic patients achieved remission according to the reduction of the YMRS score of >75% at the 8th week with a higher dose of lithium at the 8th weekend (g/day) than in the no-remission group. Manic patients with genotype GG had lower YMRS scores and lower doses and serum concentrations of olanzapine than patients with genotype AA+AG from the 4th week to the 8th week. Manic patients with genotype GG had a higher relative change in the YMRS score than those with genotype AA+AG from the 2nd week to the 8th week. No differences in HAMA or HAMD were found between the groups with genotype GG and AA+AG. There were more patients who achieved an early effective response in the 2nd week and remission in the 8th in those with genotype GG compared to those with genotype AA+AG. Manic patients with genotype GG had a greater improvement in the YMRS score due to a greater early effective response and remission, which was not related to higher doses and serum concentrations of olanzapine and lithium.